ANALISIS PERAN PANCASILA DALAM MEMBENTUK PERDAMAIAN KEBERAGAMAN DAN PERSATUAN - Arfiyansyah, Maruf; Aulia Sabrina, Azzahra; Hudi, Ilham; Hilaliyah, Nadiatul; Aprilia, Mita; Aqila, Zakiya Nada (Jurnal Pengabdian Kompetitif, 2024)
Pancasila is the foundation and ideology of the Indonesian nation and has a function in the life of the Indonesian nation and state. The meaning of Pancasila includes fundamental values that strengthen diversity, unity, and integrity in the midst of Indonesia's diverse ethnic, religious, cultural, and linguistic communities. In the context of the nation's future, Pancasila has great relevance in building a strong foundation for sustainable development and progress for the Indonesian nation. Pancasila has an important meaning for the future of the Indonesian nation because it is able to become a guide in achieving state goals, strengthening national unity, and creating social justice for all people. Pancasila remains relevant for the future of the nation because it is able to become a foundation for facing various challenges and changing times. Pancasila encourages sustainable, democratic, and socially just development. Pancasila is also able to be a means of strengthening national unity and avoiding horizontal conflict. In addition, Pancasila is able to maintain cultural and religious diversity in Indonesia, so as to strengthen tolerance and togetherness between citizens